2016
DOI: 10.1002/chem.201602451
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates Formed in the Reactions of Organocuprates with α,β‐Unsaturated Nitriles

Abstract: Conjugate additions of organocuprates are of outstanding importance for organic synthesis. To improve our mechanistic understanding of these reactions, we have used electrospray ionization mass spectrometry for the identification of the ionic intermediates formed upon the treatment of LiCuR2 ⋅LiCN (R=Me, Bu, Ph) with a series of α,β-unsaturated nitriles. Acrylonitrile, the weakest Michael acceptor included, did not afford any detectable intermediates. Fumaronitrile (FN) yielded adducts of the type Lin-1 Cun R2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“… Given that it has been established from organocopper chemistry that one way of stabilizing a neutral organocopper complex, RCu (R = alkyl or aryl) is the addition of an organolithium, RLi, to form a lithium ate complex, Li + [CuR 2 ] − , it is surprising that there are no reported attempts at preparing the related borohydride ate complexes Li + [Cu­(BH 4 ) 2 ] − . Inspired by the extensive studies of Koszinowski that have demonstrated the power of using negative-ion electrospray ionization to probe organocuprates, here we survey the formation of copper ate complexes containing coordinated borohydride. We use electrospray ionization tandem mass spectrometry ((−)­ESI-MS) in an ion-trap mass spectrometer , to establish the stoichiometry (types of ligand and nuclearity) of such complexes, and we study their gas-phase fragmentation reactions under collision-induced dissociation (CID) conditions.…”
Section: Introductionmentioning
confidence: 99%
“… Given that it has been established from organocopper chemistry that one way of stabilizing a neutral organocopper complex, RCu (R = alkyl or aryl) is the addition of an organolithium, RLi, to form a lithium ate complex, Li + [CuR 2 ] − , it is surprising that there are no reported attempts at preparing the related borohydride ate complexes Li + [Cu­(BH 4 ) 2 ] − . Inspired by the extensive studies of Koszinowski that have demonstrated the power of using negative-ion electrospray ionization to probe organocuprates, here we survey the formation of copper ate complexes containing coordinated borohydride. We use electrospray ionization tandem mass spectrometry ((−)­ESI-MS) in an ion-trap mass spectrometer , to establish the stoichiometry (types of ligand and nuclearity) of such complexes, and we study their gas-phase fragmentation reactions under collision-induced dissociation (CID) conditions.…”
Section: Introductionmentioning
confidence: 99%